PENGARUH KARAKTERISTIK PEKERJAAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI - Prassuari, Putri Yana; Hamdi, Nizar; Bairizki, Ahmad (Valid Jurnal Ilmiah, 2019)
This study aims to determine the influence of both partial and simultaneous about the characteristics of work and work environment on employee job satisfaction on PT Bank Rakyat Indonesia (Persero) Tbk, branch of Mataram. The type of research used in this study is an associative research. The sample in this study is the total number of employees of PT. Bank Rakyat Indonesia (Persero) Tbk, Branch of Mataram. While data analysis is generated through SPSS using multiple linear regression analysis, partial determination, F test and t test. The results showed that job characteristics and work environment have a significant effect on job satisfaction. Simultaneously through F test, work characteristics and work environment have a significant effect on job satisfaction where the value of f count is higher than f table that is equal to 171.098 > 3.20. Work environment is the most dominant variable to affecting employee job satisfaction. The result of coefficient of determination also shows that the ability of independent variable consisting of work characteristic and work environment in explaining variation of dependent variable is considered high enough. It can be seen from the analysis of the coefficient of determination that is equal to 0.876 or 87.6%. Furthermore, the residual value of adjusted R square (0.124 or 12.4%) is the influence by other variables which is not included in this research study.